Argumentation as pedagogy for social justice through science education - Edwards , N (South African Journal of Higher Education, 2011)
Teachers are the curriculum implementers in the classroom, which can become either a constraining or transformative environment. In this article Bourdieu’s notion of habitus is appropriated to illustrate the transformative potential of the teacher in the classroom. Paulo Freire’s problem-posing education is also utilised as it opens up the space for a dialogical encounter in the classroom. It is then suggested that argumentation as pedagogy in science education is dialogical by nature and can contribute towards social transformation. Debates about socio-scientific issues in the public domain require the skills that argumentation promotes and it is proposed that social justice pedagogy can make a contribution.